Olfactory function in young adolescents with Down's syndrome. - McKeown, D A (1996)
Decreased ability to smell is present in adults with Down's syndrome, many of whom are known to have brain pathology analogous to that seen in Alzheimer's disease. Because olfactory loss is well documented in Alzheimer's disease, the question arises whether young adolescents with Down's syndrome, who have no clear Alzheimer's disease-like neuropathology, also exhibit olfactory dysfunction. To consider this issue, standardised tests of odour discrimination and identification were administered to 20 young adolescents with Down's syndrome (mean age (SD) 13.89 (1.98) years) and their test scores were compared with 20 mentally retarded and 20 non-mentally retarded control subjects matched to the patients with Down's syndrome on the basis of cognitive ability. No significant differences in olfactory function were found among the three study groups. These findings, along with those from studies of olfactory function in older patients with Down's syndrome, suggest that Down's syndrome related olfactory dysfunction occurs only at ages when Alzheimer's disease-like pathology is present.